Dietary prebiotic combination improves immunological and hematological parameters in weaned pigs - Arantes Alvarenga, Patrícia Versuti [UNESP]; Cambito de Paula, Vinicius Ricardo [UNESP]; Dib Saleh, Mayra Anton [UNESP]; Ferreira, Silvia Letícia [UNESP]; Telles, Filipe Garcia [UNESP]; de Oliveira Orsi, Ricardo [UNESP]; Padovani, Carlos Roberto [UNESP]; Ruiz, Urbano dos Santos; Panhoza Tse, Marcos Livio [UNESP] (Elsevier, 2025)
As antimicrobial resistance is a global public health problem and as known the use of prebiotics on animal nutrition have antimicrobial effects, we hypothesized the use of prebiotic additives can be an alternative to in-feed antibiotics for piglets to control sanitary challenge. Thus, the aim of this study was to evaluate the inclusion of prebiotics mannan-oligosaccharide (MOS), β-glucan, fructooligosaccharide (FOS) and galacto-oligosaccharides (GOS) to replace antibiotics as growth promoters, on immunological and hematological parameters of 21d-old weaned pigs challenged with intramuscular injection of 30 μg kg−1 body weight of Escherichia coli lipopolysaccharide (LPS). Forty weaned piglets (7.2 kg) fed: CON = basal diet (BD) plus 120 ppm of halquinol; Mβ = BD plus a blend of MOS and β-glucan; F9G1 = BD plus a blend of MOS and β-glucan and a blend of FOS/GOS (ratio 9:1); F7G3 = BD plus a blend of MOS and β-glucan and a blend of FOS/GOS (ratio 7:3); F5G5 = BD plus a blend of MOS and β-glucan and a blend of FOS/GOS (ratio 5:5). After LPS challenge, the animals fed F9G1 had higher hydrogen peroxide (H2O2) and the same nitric oxide (NO) serum concentration than CON. Animals fed Mβ and F9G1 showed similar serum C-reactive protein (CP) concentration than CON and serum cytokine tumor necrosis factor alpha (TNF-α) concentration were higher in animals fed F9G1 or F5G5 than CON. In general, we concluded that treatment F9G1, is better for immune response during immunological challenge, because more effective immunological variables were affected (H2O2, NO, CP and TNF-α).
Keywords: Health; Immunity; Prebiotics; Swine